2012
DOI: 10.1007/s11033-012-1889-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of NDRG1 expression in oral and oropharyngeal squamous cell carcinoma

Abstract: Human N-myc downstream-regulated gene 1 (NDRG1) is a metastasis suppressor gene with several potential functions, including cell differentiation, cell cycle regulation and response to hormones, nickel and stress. The purpose of this study was to investigate the immunoexpression of NDRG1 in oral and oropharyngeal squamous cell carcinomas searching for its role in the clinical course of these tumors. We investigated immunohistochemical expression of NDRG1 protein in 412 tissue microarray cores of tumor samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…. Regarding OSCC, NDRG1 has been shown to repress cancer cell growth and invasion, and has a positive correlation with survival of OSCC patients . Our data clearly showed that CAPE treatment increased NDRG1, but not NDRG2 and NDRG3, protein expressions in both SAS and OECM‐1 cells (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…. Regarding OSCC, NDRG1 has been shown to repress cancer cell growth and invasion, and has a positive correlation with survival of OSCC patients . Our data clearly showed that CAPE treatment increased NDRG1, but not NDRG2 and NDRG3, protein expressions in both SAS and OECM‐1 cells (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The importance of NDRG1 expression has been examined in SCCs of the internal organs, in the literature. Dos Santos et al [18] showed significant upregulation of NDRG1 in oral and oropharyngeal SCCs, and concluded that NDRG1 overexpression was significantly correlated with long-term survival. Similar results were also reported by Chang et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…Also known as n-myc downstream-regulator protein 1, NDRG1 is a metastasis suppressor gene that inhibits the NF-κB (nuclear factor-κB) pathway, thus inhibiting functions such as angiogenesis, proliferation, migration and invasion [24]. Its over-expression in OSCC has been linked in one study with long-term specific survival [25]. As the n numbers were small in our study, with three stage I and four stage IVa tumours, more investigation will be required to validate these results, especially with regards to the relatively unknown KIAA1217.…”
Section: Proteomic Comparisonsmentioning
confidence: 99%